AB1024 Ultrasound in giant cell arteritis: cut-off and pitfalls in the halo sign. (15th June 2017) - Miguel, E De; Beltran, LM; Monjo, I; Deodati, F; Schmidt, WA; García-Puig, J
Abstract : Background: At the age of presentation of Giant Cell Arteritis (GCA) atherosclerosis is common. The ultrasonographic (US) appearance of athermanous plaque is usually easily differentiated from the hypoechoic halo of GCA. However, the US appearance of the increased of the intima-media-thickness (IMT) in an atherosclerotic carotid artery may have similar image appearance as the halo sign. We hypothesize that atherosclerosis could produce an increase of temporal artery (TA) IMT and cause false-positives halo sign. Objectives: The aim of this study was to explore the better cut-off in the IMT of TA to minimise the number of false-positive GCA diagnosis caused by atherosclerosis. Methods: Consecutive non selected patients, ≥50 years-old with high vascular risk according to European Guidelines on cardiovascular disease prevention, and without signs or symptoms of GCA, were included. Ultrasonography of carotid artery: Carotid US examinations were performed on a Mylab Seven (Esaote Medical Systems, Italy) with a 4–13 MHz linear-array. The system employed dedicated software radiofrequency-tracking technology to obtain IMT (QIMT®). Ultrasonography of temporal superficial artery: A color Doppler ultrasound (CDU) and grey scale measure of the IMT/halo sign in both TA and its branches was performed by a second experienced sonographer. A Mylab Twice equipment (Esaote, Geneve, Italy) was used, with a 22 MHz frequency for grey scale and a 12.5 MHz for CDU (color gain of 51, PRF of 2 kHz). The sonographer was blind to the clinical and carotid ultrasound IMT data. Results: Forty patients were studied, 28 men (70%), with a mean age of 70, 6±6, 9 years. Three patients were active smokers and 27 ex-smokers. Arterial hypertension was present in 39 (97.5%), dyslipidaemia in 34 (85%) and diabetes in 19 (47.5%). The mean erythrocyte sedimentation rate was 13.6±11.0. The table shows that an IMT >0.30 mm (halo sign) was seen in at least 1 TA branch of 18 patients (45%) with 33 TA branches affected (20.6%). An IMT cut-off >0.34 mm, was present in 4 patients (10%). When at least two affected branches with this measure were required to make the US diagnosis (criteria recommended to improve specificity) only one patient (2.5%) produced a false-positive halo sign. Conclusions: To the best of our knowledge, this is the first communication indicating that atherosclerosis is a potential cause of false-positive halo sign. We propose a cut-off of AT IMT >0.34 mm in at least two branches to minimise the number of false positives in GCA diagnosis. Disclosure of Interest: None declared